How to Encourage Student Voice: Obtaining Effective Feedback from Law Students in Course Evaluation - Vicci Y.J. Lau (Legal Education Review)
Effective feedback allows teachers to review, reflect and improve their teaching practices. Students’ feedback is key to teachers’ reflection as they are an important stakeholder in the teaching and learning community. In order for students’ feedback to foster teachers’ critical self-reflection, it is crucial to establish an appropriate opportunity and method to motivate students to provide effective feedback. This article seeks to investigate whether mid-term student evaluations, which are conducted in the middle of the term when the course is taught half-way through, provide a potentially better or alternative opportunity in obtaining honest and effective student feedback so that teachers can hear student voice. This article reports on the findings of an empirical study on both the students’ and teachers’ perceptions on mid-term student evaluations implemented in a few post-graduate law courses at The University of Hong Kong. A total of 73 students and 9 teachers participated in and completed the surveys of this study during the academic years of 2017-2019. The findings suggest that the key factors in motivating the students to provide honest feedback through the mid-term student evaluations are the perceived benefit to the students themselves and their belief that their teachers care about their feedback. This article argues that mid-term student evaluations advance perceived caring of the teachers by showing that the teachers are empathetic, understand and respect students’ views, and are responsive and react to student needs when they listen to what the students say. The findings suggest, however, that the teachers did not perceive the mid-term student evaluations as positively as the students, but the teacher participants believed that they had received generally constructive feedback from their students through mid-term student evaluations. Based on the results of empirical analysis, this article proposes a ‘motivation-driven student evaluation cycle’ which provides a more comprehensive model in setting out the crucial and ideal steps in a student evaluation process to achieve enhancement in students’ learning and teachers’ teaching effectiveness. If both the students and the teachers have more motivation to participate in this evaluation cycle through mid-term student evaluations, then mid-term student evaluations will be instrumental in enhancing teaching and learning.